Educational Supply Chain Management System: A Case Study in Indonesia - Kyaw Zay-Ya; Fahmi Rizal; Anugrah Agung Ramadhan; Mandalika Mandalika (International Journal of Supply Chain Management, 2021)
This study aims to explore the Educational Supply Chain Management System existing in the case faculty by using the sequential mixed methods (qualitative-quantitative). The use of mixed methods in this work not only captures the full picture of the comprehensive research results but also fills the gap in the existing literature. Purposive sampling method and simple random sampling method were used for selecting the participants. The target population involved academicians and management practitioners. The number of participants for qualitative was 48 and 50 respondents for the quantitative method. A semi-structured interview with at least 20 questions was used and 40 minutes was consumed on average per interview. Thematic analysis was employed for qualitative data analysis. Qualitative phase resulted in five primary activities involving input, operation, output, public relations, and services, and four supporting activities consisting of procurement, technology management, human resources, and infrastructure management (finance and student affairs). Based on these results, nine themes were developed to build quantitative instruments which included 38 Likert Scales questions. Pearson’s R-Table method was used for instrument validity test and Cronbach Alpha Coefficient was applied to test instrument reliability. The data from the respondents were analyzed by Percentage Analysis method. Measurement level of all indicators achieved over 65% and thus, nine supply chain functions (qualitative results) have firmly identified by quantitative method as the existing functions. Therefore, this research gives the sufficient research findings of how the Educational Supply Chain works in the educational institution.